Construction of Mikusinski operational calculus based on the convolution algebra of distributions. Basic provisions - Iosif L Kogan (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2012)
The main provisions of the operational calculus based on the convolution algebra of distributions D+ and D− that extends this method to the negative values of the argument are given. The relation between the proposed method and the classical operational calculus built on the Laplace transform is provided.